2017
DOI: 10.1016/j.desal.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of brine management methods: Zero-discharge desalination and salinity-gradient power production

Abstract: Growing desalination capacity worldwide has made management of discharge brines an increasingly urgent environmental challenge. An important step in understanding how to choose between different brine management processes is to study the energetics of these processes. In this paper, we analyze two different ways of managing highly saline brines. The first method is complete separation with production of salts (i.e., zero-discharge desalination or ZDD). Thermodynamic limits of the ZDD process were calculated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 40 publications
(72 reference statements)
0
45
0
Order By: Relevance
“…Seawater RO has been shown to be the most energy efficient [6][7][8][9][10][11][12] and lowest cost [9,13] method to desalinate seawater and produce freshwater. For the crystallization step, the state-of-the-art technology currently used are multi-effect evaporators [14]. In a previous work, some of the authors of this paper had shown that state-of-the-art crystallizers are more efficient than state-of-the-art brine concentrators and suggested that research work should focus on improving the brine concentration step [14].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Seawater RO has been shown to be the most energy efficient [6][7][8][9][10][11][12] and lowest cost [9,13] method to desalinate seawater and produce freshwater. For the crystallization step, the state-of-the-art technology currently used are multi-effect evaporators [14]. In a previous work, some of the authors of this paper had shown that state-of-the-art crystallizers are more efficient than state-of-the-art brine concentrators and suggested that research work should focus on improving the brine concentration step [14].…”
Section: Introductionmentioning
confidence: 98%
“…For the crystallization step, the state-of-the-art technology currently used are multi-effect evaporators [14]. In a previous work, some of the authors of this paper had shown that state-of-the-art crystallizers are more efficient than state-of-the-art brine concentrators and suggested that research work should focus on improving the brine concentration step [14]. For seawater brine concentration, two proven technologies that can be used are mechanical vapor compressors (MVC) systems [10,[15][16][17][18] and electrodialysis (ED) systems [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saturated brine (a sodium chloride solution of concentration above 300 g/dm 3 ) is an important resource in the chemical industry. It is usually obtained by leaching underground salt deposits or by concentration of the saline waters (seawater, water from salt lakes and mine brines) with direct thermal methods or thermal methods preceded with membrane concentration [1][2][3][4][5][6][7]. Saline water is increasingly often desalinated and concentrated with membrane methods: pressure-driven membrane processes (mainly reverse osmosis, RO) and electromembrane methods (electrodialysis, ED; electrodialysis reversal, EDR) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%